Effect of Hypertension on Childhood-onset Systemic Lupus Erythematous in a Tertiary Medical Center in Korea - Jeong Yeon Kim; Heeyeon Cho (Korean Society of Pediatric Nephrology, 2020)
Purpose The purpose of this study was to evaluate the prevalence, clinical characteristics, and long-term clinical effects of hypertension in Korean childhood-onset systemic lupus erythematous (SLE) patients. Methods The medical records of SLE patients, diagnosed by 2019 SLE European League Against Rheumatism/American College of Rheumatology (EULAR/ACR) classification criteria, who visited Samsung Medical Center from January 2009 to May 2019 were reviewed. Disease activity and long-term damage were evaluated using the Modified Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K) and the Pediatric Systemic Lupus International Collaborating Clinics/ACR Damage Index (Ped-SDI), respectively. The sex-, age- and height-blood pressure standards recommended by the American Academy of Pediatrics 2017 guideline was used to define hypertension. Results A total of 32 patients were enrolled in this study. The median follow-up duration was 7.3 years and females were predominant. The median ages at SLE and hypertension diagnoses were 14.2 and 14.3 years, respectively. The biopsy-proven lupus nephritis was detected in 90.6% and 37.5% were class IV. During the follow-up, 12 patients (37.5%) had hypertension. Among them, 2 patients had 3 episodes of posterior reversible encephalopathy syndrome and 5 patients had left ventricular hypertrophy (LVH). Univariate analysis showed baseline hypertension was significantly correlated with a lower estimated glomerular filtration rate, higher body mass index and SLEDAI at baseline. The development of hypertension during the follow-up was significantly correlated with obesity, LVH, and higher Ped-SDI. Conclusion Our study revealed that hypertension in pediatric SLE is associated with obesity and renal function at SLE diagnosis and could affect long-term damage.